Chronic almond nut snacking alleviates perceived muscle soreness following downhill running but does not improve indices of cardiometabolic health in mildly overweight, middle-aged, adults - Siegel, Leah; Rooney, Jessica; Marjoram, Lindsey; Mason, Lauren; Bowles, Elena; van Keulen, Thomas Valente; Helander, Carina; Rayo, Vernon; Hong, Mee Young; Liu, Changqi; Hooshmand, Shirin; Kern, Mark; et al. (Frontiers in Nutrition, 2024)
Introduction: As a popular food snack rich in protein, fibre, unsaturated fatty acids, antioxidants and phytonutrients, almond nut consumption is widely associated with improvements in cardiometabolic health. Limited data exists regarding the role of almond consumption in improving exercise recovery. Accordingly, we aimed to investigate the impact of chronic almond snacking on muscle damage and cardiometabolic health outcomes during recovery from eccentric-based exercise in mildly overweight, middle-aged, adults. Methods: Using a randomized cross-over design, 25 mildly overweight (BMI: 25.8±3.6kg/m 2 ), middle-aged (35.1±4.7y) males (n=11) and females (n=14) performed a 30-minute downhill treadmill run after 8-weeks of consuming either 57 g/day of whole almonds (ALMOND) or an isocaloric amount (86g/day) of unsalted pretzels (CONTROL). Muscle soreness (visual analogue scale), muscle function (vertical jump and maximal isokinetic torque/vertical jump), and blood markers of muscle damage (creatine kinase (CK) concentration) and inflammation (c-reactive protein concentrations) were measured pre and post (24, 48, and 72h) exercise. Blood biomarkers of cardiometabolic health (total cholesterol, triglycerides, HDL cholesterol, and LDL cholesterol), body composition and psycho-social assessments of mood, appetite and well-being were measured pre and post intervention. Results: Downhill running was successful in eliciting muscle damage, as evidenced by a significant rise increase in plasma CK concentration, increased perception of muscle soreness, and impaired vertical jump performance (p<0.05) during recovery. No trial order effect was observed for any outcome measurement. However, expressed as AUC over the cumulative 72h recovery period, muscle soreness measured during a vertical jump was reduced by 24% in ALMOND vs. CONTROL (p<0.05) and translated to an improved maintenance of vertical jump performance (p<0.05). However, ALMOND did not ameliorate the CK response to exercise or isokinetic torque during leg extension and leg flexion (p>0.05). No pre-post intervention changes in assessments of cardiometabolic health, body composition, mood state or appetite were observed in ALMOND or CONTROL (all p>0.05). Conclusions: Chronic almond supplementation alleviates task-specific perceived feelings of muscle soreness during acute recovery from muscle damaging exercise, resulting in better maintenance of muscle functional capacity. These data suggest that almonds represent a functional food snack to improve exercise tolerance in mildly overweight, middle-aged adults.